The Impact of Traditional Game Belempongan on Elementary Students’ Physical Fitness: A Quasi-Experimental Study (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The decline in physical activity among children, exacerbated by the COVID-19 pandemic, necessitates innovative and engaging interventions in school settings. Culturally relevant physical education methods, particularly those grounded in local traditions, may offer viable solutions to improve children’s physical health, motivation, and sense of belonging. This study aimed to examine the impact of the traditional game Belempongan on elementary students' physical fitness, measured using the Indonesian Physical Fitness Test (TKJI). A quasi-experimental pretest-posttest design was employed involving 30 students. Participants engaged in Belempongan sessions integrated into physical education over several weeks. Physical fitness components: 30-meter sprint, bent-arm hang, sit-ups, vertical jump, and 600-meter run, were measured before and after the intervention. Data were analyzed using paired sample t-tests with JASP 0.19.3, assuming normal distribution. All physical fitness indicators showed statistically significant improvements (p < .001), with very large effect sizes across components: sprint speed (d = 2.180), bent-arm hang (d = 8.050), sit-ups (d = 5.623), vertical jump (d = 3.161), and 600-meter run (d = 1.985). The overall TKJI score also improved significantly (d = 7.938). These results affirm that Belempongan not only improves measurable physical health indicators but also offers a sustainable, low-cost, and contextually meaningful alternative to conventional physical education. Traditional game-based physical education offers a culturally resonant, enjoyable, and effective method for improving children's fitness and should be considered for wider implementation within school curricula. Future studies should explore longitudinal outcomes, cross-regional comparisons, and additional psychosocial indicators to broaden the empirical foundation for culturally integrated PE programs.